Analysis of the Current Situation and Development Trends of Japanese Language Education in Chinese Universities - He, Ludan (Transactions on Social Science, Education and Humanities Research, 2024)
This article mainly analyzes the current development trend of Japanese language education in universities, analyzes the problems in current Japanese language teaching, and positions new goals for the development of Japanese language education and teaching based on the background of the new era. This article explores the development trends of Japanese language education in Chinese universities, including emphasis on practicality, cultural cultivation of students, active implementation of compound and bilingual teaching, order based training, lifelong education, etc., so that Japanese language professionals can truly serve national strategies. Cultivating composite talents with Japanese language skills ultimately enables the cultivation of Japanese language professionals to truly serve the national strategy of the 21st century.